Development of a language policy in a rural school - Fumba, Zamumzi Norman (Rhodes University, Faculty of Education, Department of Education, 2003)
The study was undertaken to observe and participate in the process and development of a language policy for a rural secondary school in Peddie in the Eastern Cape. This was done in collaboration with parents, learners, and teachers. The researcher acted as a researcher, facilitator and learner in the process that Iead to the final product. Twenty four learners were selected from Grade 8 to Grade 10. These learners formed three focus groups. A questionnaire and lesson observation were used to establish what was taking place in the school with regard to language practices and preferences by learners, teachers and parents. Lesson observations were recorded by a tape recorder. Outcomes are that Xhosa is the dominant language to which the learners are exposed. They only have the exposure to 'chunks' of English in class and when they read magazines, newspapers and listening to radio and TV. Teachers code switch. This is supported by both learners and their parents. Parents want their children to improve performance by being taught in the medium of a language they understand well enough. The study shows different perceptions about the language that should be used as LOLT. Parents in the study favour English as LOLT, while parents in general favour Xhosa. This view is also held by both teachers and learners. At a conscious level when teachers and learners talk about the language to be used as LOLT, they favour English, but when they are faced with the reality of the class they are ambivalent, hence they code switch. The study finally reports on the divergent views of the parents, on one hand, and those of the teachers and the learners on the other hand. The divergence will be resolved in a workshop, part of the broader process of school language policy research, which is beyond the scope of the research reported in the thesis. The final product, in the form of the school language policy, will then be drafted for presentation to the School Governing Body (SGB) for ratification and writing up process.
Keywords: Language policy -- South Africa; Language and education -- South Africa; Education, Rural -- South Africa -- Peddie; Black people -- Education -- South Africa; Native language and education -- South Africa